Evidence-based dentistry: An enigma or a solution - Vikas Jindal (Wolters Kluwer Medknow Publications, 2016)
Evidence based dentistry (EBD) is often misinterpreted or the very essence of its meaning is being lost on the practitioners. This concept has been in dentistry for around two decades. Today's era witnesses information explosion and consumer awareness which is further facilitated by internet development. EBD is a logical, common-sense, patient-oriented approach that is not different from the regular treatment except that it takes into consideration the uniqueness of each patient and finding the right treatment for him by studying the available authentic literature available with similar case scenario. There is a great mass of information that can help us in our patient care decisions but the question remains regarding the authencity of it. Thus only the well trusted sites such as Cochrane library or the Pubmed should be trusted. It is important for dentists to be able to keep up with developments in diagnosis, prevention and treatment of oral disease, as well as newly discovered causes of diseases, especially in regards to patient safety. Correct appraisal of the available literature for a particular clinical situation if properly inculcated in our practice can make huge difference in our approach. This article is an review regarding the approach towards evidence based dentistry and using it for better results.